Irrigation Water Management by Using Remote Sensing and GIS Technology to Maintain the Sustainability of Tourism Potential in Bali - Putu Aryastana; Cok Agung Yujana; I Made Ardantha (Journal of Infrastructure & Facility Asset Management, 2020)
This paper reviews the literature on the potential use of remote sensing and GIS technology in irrigation water management to support the preservation of the Subak irrigation system in Bali. Subak is a system that has survived for a very long time faces challenges in irrigation water management. Remote sensing technology provides an opportunity to get identification, analysis, and monitoring of land use, irrigation area, irrigation infrastructures, water supply source, water use, crop type, water rights, irrigation scheduling, yield estimates, nursery monitoring, crop disease detection, evaluate fruit maturity, and detection of bruises on fruit. The integration of remote sensing technology and GIS is expected to be able to make irrigation infrastructure assets and water management more effective and efficient.